Clinical and coronary angiographic profiling in young patient with acute ST-elevation myocardial infarction admitted in cardiac critical care unit of tertiary care centre at south Tamil Nadu - Visnudas, M. S.; Edwin, J. M. Ravichandran; Viswanathan, T. (International Journal of Advances in Medicine, 2023)
Background: Premature coronary artery disease (PCAD) is associated with a high rate of ischemic recurrence and mortality, causing a significant impact on public health. The present study focuses on the assessment of the risk factors, clinical presentation, angiographic profiling considering severity, and management of extremely young adults (aged ≤45 years) affected with first ST elevation acute myocardial infarction (STEMI). Methods: The current study (cross-section) was carried out among 94 consecutive patients with STEMI. The study on patients was carried out between January 2022 and June 2022 at Tirunelveli Medical College Hospital, department of cardiology. Results: This study involved 94 patients with a mean age of 37.80 years, 8.5% <25, and 84.9% male patients. Risk factors included smoking, being overweight, diabetes, hypertension, chest pain, syncope, and obstructive coronary artery disease (CAD). The most common symptom was chest pain (98.9%). Left anterior descending (LAD) was the most common culprit artery (26.1%), and ostial LAD was (3.2%). Percutaneous coronary intervention (PCI) was done in 53.2% of patients, elective PCI was 26.6%, pharma co-invasive PCI was 24.5%, and primary PCI was 2.1%. The patient was referred to coronary artery bypass grafting was 10.6%. 23.4% of patients had recanalized and normal coronaries, and 36% received medical management. No mortality occurred in this study. Conclusions: Most commonly, AMI is found in very young male adults, and smoking is the commonly associated risk factor. LAD artery involvement was the leading cause of AWMI and the most common presentation observed.